The scientific achievement of the Middle Ages - Dales, Richard C. (University of Pennsylvania Press, 1973)
The scientists of the twelfth century were daring, original, inventive, and above all determined to discover purely rational explanations of natural phenomena. Their intense interest in the natural world for its own sake, their habits of precise observation, and the high value they place on man as a rational being portend a new age in the history of scientific thought. This book offers a comprehensive sampling of medieval scientific thought in the context of an historical narrative.